Diffusion-weighted imaging of the brain in children with tuberous sclerosis complex: A comparative study - Atalar, Mehmet H.; Şener, Rıfat Nuri (Journal of Pediatric Neuroradiology, 2012)
To evaluate diffusion imaging characteristics of parenchymal changes in patients with tuberous sclerosis complex (TSC) compared with those in control subjects. We reviewed magnetic resonance imaging (MRI) and diffusion-weighted imaging (DWI) findings in six patients diagnosed with TSC. MRI examinations were performed in a 1.5 Tesla MRI unit using a transmit/receive coil with T1-weighted and T2-weighted spin-echo and fluid-attenuated inversion recovery sequences. DWI MRI was obtained using an echo-planar imaging sequence. Apparent diffusion coefficient (ADC) values were measured. In addition, five normal children were studied for comparison. ADC was higher in cortical tubers than in the corresponding cortical location of controls (p < 0.05). ADC values were higher in white-matter lesions and perilesional white matter than in the contralateral normal-appearing white matter of both patients and controls (p < 0.05). There were no differences for ADC values between the normal-appearing white matter of patients with TSC and control subjects. It appears that DWI MRI can be useful in the evaluation of parenchymal changes associated with TSC.
Keywords: Tuberous sclerosis complex; brain; MRI; diffusion-weighted imaging; apparent diffusion coefficient values